The Spiritual Entrepreneur of The Santri Based On Falsafah Local Wisdom Gusjigang In The City of Kudus - Bayu Tri Cahya; Saidatul Munawwaroh; S Surepno; Irsad Andriyanto (Universitas Darussalam Gontor, 2021)
The Kudus Regency society is known as the santri's merchant is so persistent, skilled, and hardworking. The personage of Sunan Kudus is characterized as waliyul Ilmy and this Guardian teaches a philosophy